Respuesta :
Answer:
A
Step-by-step explanation:
let the number be x, then
the difference of x and 6 is x - 6 and
5 times the sum of x and 2 is 5(x + 2)
Equate both expressions
5(x + 2) = x - 6 ← distribute left side
5x + 10 = x - 6 ( subtract x from both sides )
4x + 10 = - 6 ( subtract 10 from both sides )
4x = - 16 ( divide both sides by 4 )
x = - 4 → A
Option A is correct. The unknown number according to the question given is -4
Let the unknown number be "x"
- The difference of the number and 6 is expressed as x - 6
- 5 times the sum of the number and 2 is expressed as 5(x+2)
Equating both results to get the unknown
x - 6 = 5(x+2)
Expand
x - 6 = 5x + 10
Collect the like terms
x - 5x = 10 + 6
-4x = 16
x = 16/-4
x = -4
Hence the unknown number according to the question given is -4
Learn more here: https://brainly.com/question/13644947